2020
DOI: 10.3324/haematol.2019.240754
|View full text |Cite
|
Sign up to set email alerts
|

Potential targeting of FLT3 acute myeloid leukemia

Abstract: Aberrant FLT3 receptor signaling is common in acute myeloid leukemia (AML) and has important implications for the biology and clinical management of the disease. Patients with FLT3-mutated AML frequently present with critical illness, are more likely to relapse after treatment, and have worse clinical outcomes than their FLT3 wild type counterparts. The clinical management of FLT3-mutated AML has been transformed by the development of FLT3 inhibitors, which are now in use in the frontline and relapsed/refracto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 106 publications
0
62
0
Order By: Relevance
“…Mutant FLT3 contained two kinds of mutation forms, internal tandem duplication (ITD) in juxtamembrane domain and point mutation within the activation loop of tyrosine kinase domain (TKD) [2] . FLT3 mutation occurred in 30% of de novo AML patients and accounted for the most predominant mutation type in AML [1] . Notably, FLT3-ITD was considered as an independent unfavorable risk factor in AML, for patients with FLT3-ITD always be resistant to chemotherapy and present a higher relapse rate and more early death cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutant FLT3 contained two kinds of mutation forms, internal tandem duplication (ITD) in juxtamembrane domain and point mutation within the activation loop of tyrosine kinase domain (TKD) [2] . FLT3 mutation occurred in 30% of de novo AML patients and accounted for the most predominant mutation type in AML [1] . Notably, FLT3-ITD was considered as an independent unfavorable risk factor in AML, for patients with FLT3-ITD always be resistant to chemotherapy and present a higher relapse rate and more early death cases.…”
Section: Discussionmentioning
confidence: 99%
“…FMS-like tyrosine kinase 3 (FLT3) is a type 3 receptor tyrosine kinase. Certain alteration of this protein can constitutively active receptor tyrosine kinase causing uncontrolled proliferation, reduced apoptosis, and malignant transformation of myeloid cells [1] . Thus, mutant FLT3 is well known as a promising target for molecular therapy in acute myeloid leukemia (AML) [1,2] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond the support for upfront use of midostaurin observed in the RATIFY trial, it has been suggested ( 6 , 18 ) that the optimal sequencing of FLT3-inhibition may be to utilize multikinase inhibitor in the upfront setting when the disease is known to be polyclonal ( 19 ) and to save a more targeted FLT3 inhibitor for the time of relapse when the disease may have fewer clones and may be more dependent on FLT3 signaling. It is important to note that this suggestion is merely theoretical.…”
Section: Discussion: Which Flt3 Inhibitor Should Be Used For Upfront mentioning
confidence: 99%
“… 2 The presence of FLT3 -ITD is predictive for response to FLT3-TKIs, 3 yet 41%–56% of FLT3 -WT patients respond to FLT3 -TKIs, indicating alternative possibilities of FLT3 pathway activation or TKI off-target effects leading to unexpected treatment response. 4 Others have identified genomic and global phosphorylation markers associated with FLT3-TKI response in FLT3 -WT AML. 5 , 6 As the primary targets of currently approved FLT3-TKIs are tyrosine (Y) kinases, we hypothesized that the direct evaluation of tyrosine kinome could reveal phosphorylation markers associated with FLT3-TKI response.…”
mentioning
confidence: 99%